Літератори й театрали між УНР та Директорією - Омельчук, О. (Слово і Час, 2020)
Вивчення мистецької спадщини і творчого повсякдення 1918 року суттєво доповнює біографії низки українських письменників і коригує уявлення про вітчизняний літературний процес загалом. Велика кількість
ідей, тем, творчих пошуків цього часу стали прологом до культурного
діалогу наступних років, будучи водночас закоріненими в дореволюційний мистецький розвиток. Попри складну політичну ситуацію, 1918
рік позначений не лише активною творчою діяльністю, а й повсякчасними спробами унормувати триб мистецького життя відповідно до
правових законів і комерційної логіки. Як приклад, авторка статті
реконструює деякі аспекти театрального й літературного життя
1918 року, що висвітлювалися на сторінках київської щоденної газети «Відродження» й у таких періодичних виданнях, як «Робітнича
газета», «Нова рада», «Народна воля» та ін. Головну увагу приділено публікаціям Якова Савченка, Леся Курбаса, Михайля Семенка, а
також полеміці між представниками Молодого театру, Театральної ради, військового товариства «Батьківщина». Studying the artistic heritage and creative life in 1917—1919 significantly complements the biographies of many Ukrainian writers and influences the usual perceptions of the Ukrainian literary process overall. Against the backdrop of this period, the proletarian cultural conception no longer seems to be all-inclusive. After all, a great number of ideas, themes, and creative pursuits of 1917—1919 became a prologue to the cultural dialogue of the following years, being at the same time rooted in pre-revolutionary artistic development. For the Soviet political and cultural memory the establishment of Ukrainian statehood in 1917—1919 becomes a traumatic memory for a long time. As the present paper shows, the process over the Union of Liberation of Ukraine (SVU) in 1929—1930 was a perversion of the solemn action in honor of the short-lived triumph of the Directory of the Ukrainian People’s Republic in 1918, and in general became the quintessence of the political and symbolic delegitimization of the ‘Petliurian’ and ‘Hetmanian’ history. Despite the difficult political situation, 1918 was marked not only by vibrant creative life, but also by the daily attempts to normalize the course of artistic activity in accordance with legal laws and commercial logic. As an example, the author of the paper reconstructs some aspects of the theatrical and literary life of 1918, which were covered on the pages of the Kyiv daily newspaper “Vidrodzhennia” and also such periodicals as “Robitnycha Hazeta”, “Nova Rada”, “Narodna Volia”, etc. The paper focuses on the publications by Yakiv Savchenko, Les Kurbas, Mykhail Semenko and public polemics between representatives of “Molodyi Teatr”, “Teatralna Rada”, and the Military Society “Batkivshchyna”.